Ichneumonidae, Ethelurgus. México, parasitoid. - Kasparyan, Dmitri R.; Ruíz Cancino, Enrique (Instituto de Ecología, A.C., 2000)
A new species of geline ichneumonid, Ethelurgus annulicornis sp. nov. is described from Reserve "El Cielo", Tamaulipas, México. This species can be easily distinguished from the other species in tlie genus by its colour, it is the oniy species with a white ring on the antenna and a palé fulvous body with the head and dorsum of the mesosoma black. E. syrphicola syrphicola (Ashmead) is recorded from México.